Broadband Coupler Manipulation Through Particle Swarm Optimization for Arrayed Waveguide Grating Based Optical Coherence Tomography - Benedictus Yohanes Bagus Widhianto; Yi-Ting Lu; Wei-Chien Chang; Shih-Hsiang Hsu (IEEE Photonics Journal, 2021)
The state-of-the-art optical coherence technology (OCT) has its limitation, such as bulky and quite expensive. Miniaturization and integration of the OCT system are promising to get a compact, less costly, and more stable device. In this paper, we report the influence of optical power splitting on the sensitivity and axial resolution in spectral-domain OCT (SD-OCT) on silicon chip using tandem Mach-Zehnder directional coupler (MZDC) based broadband coupler through particle swarm optimization (PSO). A less-flat wavelength response from a broadband coupler in an interferometer for SD-OCT on-chip will decrease the sensing sensitivity. The arrayed waveguide grating (AWG) as a spectrometer in SD-OCT typically suffers from the axial resolution degradation due to the non-flat free spectrum range (FSR). To avoid the higher optical loss from the large FSR, the PSO manipulation in MZDC is then proposed to demonstrate U-shaped wavelength compensation on the non-flat AWG spectrum. With the broadband coupler configuration, a SD-OCT on-chip can maintain the sensitivity and axial resolution performance.